Pengaruh Pembebanan Awal dan Shot PeeningTerhadap Perilaku Ketahanan Lelah Baja Poros SNCM431. - Perpustakaan UGM, i-lib ([Yogyakarta] : Biro Administrasi Kemahasiswaan UGM, 2001)
This study aims to investigate the effects of pre-loading and shot peening on the fatigue resistance behavior of axle steel SNCM431. The specimens were given two sequential heat treatments, i.e. 860Â°C for 10 minutes followed by oil quench and 600"C for 2 hours then air-cooled. The specimens were polished to a certain grade before testing to produce mirror-like finish. The specimens were classified into five treatments